The effect of preventive measures to reduce the decision to delivery interval in women undergoing emergency caesarean section - Sahithi, Donthireddy L.; Talathi, Manju A.; Taralekar, Vaishali S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Time interval between the decision to perform an emergency caesarean (ES) section and the actual delivery is known as decision delivery interval (DDI). A third phase delay in the delivery of emergency obstetric care is caused by prolonged DDI. In an effort to reduce maternal morbidity and neonatal morbidity and mortality, it is essential to implement interventions designed to reduce DDI. Methods: This study was carried out to reduce DDI by setting benchmarks for all categories according to Royal College of Obstetricians and Gynaecologists (RCOG) guidelines 2010, in our setup. The study carried out in 2 phases; first phase was a pilot study comprising of 143 women who underwent ES section. The deviation in DDI with possible causes were noted. The benchmarks were set to 8%, 30% and 20% for categories 1, 2, and 3 respectively. Corrective actions were taken including both hospital and patient causes for delay and were discussed at each level. Second phase included total 460 women from January to December 2021 and evaluated for DDI. Results: Out of 460, 87 (18.91%) women had deviated from the set DDI. The percentages in individual categories 1, 2 and 3 were 17.22%, 30.50%, and 29.50%, respectively. The deviation percentage of DDI in category 2, was achieved as per benchmark set in a pilot study, however, it was not achieved for other categories. Conclusions: Since the result that was obtained didn’t reach the set deviation percentage, we have observed that achieved deviation cannot be further reduced as our clinical setup is a teaching institute.